2015
DOI: 10.1074/jbc.m115.650705
|View full text |Cite
|
Sign up to set email alerts
|

Differentially Expressed MicroRNA-483 Confers Distinct Functions in Pancreatic β- and α-Cells

Abstract: Background: MicroRNAs are noncoding RNAs and have emerged as important regulators in ␤-cell function. Results: miR-483 is highly expressed in ␤-cells but expressed at much lower levels in ␣-cells, and increased miR-483 induces insulin production in ␤-cells while repressing glucagon production in ␣-cells. Conclusion: miR-483 has opposite effects in ␣-and ␤-cells by targeting SOCS3. Significance: miR-483 is a potential therapeutic target for diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 69 publications
1
38
0
Order By: Relevance
“…Inactivation of miR-375 in mice is associated with reduced ␤-cell mass, increased ␣-cell number and plasma glucagon levels, hyperglycemia, reduced insulin secretion, and disrupted islets architecture (64). miR-483 also shows similar patterns of regulation of insulin and glucagon secretion (53). Downregulated expression of miR-375 in ob/ob mice results in reduced ␤-cell mass and plasma insulin levels and severe diabetes.…”
Section: Regulation Of ␤-Cell Development and Insulin Secretion By MImentioning
confidence: 85%
See 1 more Smart Citation
“…Inactivation of miR-375 in mice is associated with reduced ␤-cell mass, increased ␣-cell number and plasma glucagon levels, hyperglycemia, reduced insulin secretion, and disrupted islets architecture (64). miR-483 also shows similar patterns of regulation of insulin and glucagon secretion (53). Downregulated expression of miR-375 in ob/ob mice results in reduced ␤-cell mass and plasma insulin levels and severe diabetes.…”
Section: Regulation Of ␤-Cell Development and Insulin Secretion By MImentioning
confidence: 85%
“…On the other hand miR-29b was ubiquitously expressed in all tested tissues. miR-375 and miR-483 are remarkable examples of differential miRNA-mediated intrapancreatic regulation, as they stimulate insulin secretion by ␤-cells and decrease glucagon secretion by ␣-cells (53,64).…”
Section: Conservation and Specificity Of Mirna Expression Across Multmentioning
confidence: 99%
“…miRNAs play a crucial role in organ formation during embryogenesis, including pancreas development and β-cell differentiation (14). Moreover, they display an important role in maintaining functional β-cell mass (1517) and endocrine cell identity (18,19) during adult life.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs control the expression of many genes and are involved in a variety of crucial biological processes, which include development, differentiation, apoptosis, cell proliferation and diseases . Recently, a number of studies have demonstrated that miRNAs can regulate the development of pancreatic cells .…”
Section: Introductionmentioning
confidence: 99%